The Effect of Flash Sales and Free Shipping on Impulse Buying Among Tiktok Shop Users on Students in Mataram City - Agustina, Fitria Ika; Saputra, Agus Marjan; Hudairi, Ahmad (Business Management, 2025)
This study aims to examine and analyze the influence of Flash Sale and Free Shipping on Impulse Buying among TikTok Shop users, specifically university students in Mataram City. This research uses a quantitative approach. The sample size in this study consists of 100 respondents. The sampling technique used is non-probability sampling.The data analysis in this study employs multiple linear regression analysis, validity and reliability tests, and classical assumption tests, including normality test, multicollinearity test, and heteroscedasticity test, as well as hypothesis testing. All data were processed using SPSS Statistics 21. The results of the study indicate that the independent variable Flash Sale has a positive and significant effect on the dependent variable Impulse Buying, while the independent variable Free Shipping does not have a positive and significant effect on Impulse Buying.